2017
DOI: 10.18553/jmcp.2017.23.6.700
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Management and Outcomes in Patients with Nonvalvular Atrial Fibrillation Within an Integrated Health Care System

Abstract: This research and manuscript were funded by Bristol-Myers Squibb Company and Pfizer. Authors from Bristol-Myers Squibb Company and Pfizer participated in the design of the study, interpretation of the data, review/revision of the manuscript, and approval of the final version of the manuscript. An received a grant for research support from Bristol-Myers Squibb/Pfizer. Niu, Rashid, and Zheng received a grant from Bristol-Myers Squibb/Pfizer to their institutions for salary reimbursement. Vo, Singh, and Aranda ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…A five-year study in United States in non-valvular atrial fibrillation patients on warfarin revealed that around two-thirds had at least one warfarin dose adjustment annually and annual attrition rate ranged between 3.3 and 6.3 %. [15] Except for one definition, that necessitates same warfarin dose at three consecutive clinic visits over a minimum period of 3 months with PT-INR in the therapeutic range, all other definitions were observed to have reasonable agreements in the present study. Hence, the IWPC algorithm [3] may not have any bias associated with inclusion of studies and can be evaluated in other studies.…”
Section: Discussionsupporting
confidence: 56%
“…A five-year study in United States in non-valvular atrial fibrillation patients on warfarin revealed that around two-thirds had at least one warfarin dose adjustment annually and annual attrition rate ranged between 3.3 and 6.3 %. [15] Except for one definition, that necessitates same warfarin dose at three consecutive clinic visits over a minimum period of 3 months with PT-INR in the therapeutic range, all other definitions were observed to have reasonable agreements in the present study. Hence, the IWPC algorithm [3] may not have any bias associated with inclusion of studies and can be evaluated in other studies.…”
Section: Discussionsupporting
confidence: 56%
“…Oral anticoagulation medications in use within KPNC during the study period were warfarin and dabigatran, warfarin being the drug of choice at the time. Furthermore, each facility had its own pharmacy-managed, phone-based Outpatient Anticoagulation Service that managed outpatient warfarin use and provided close follow-up and monitoring of these patients, akin to similar programs in other KP regions in the U.S. 39 , 40 The percent time in therapeutic range for the international normalized ratio during the study period varied by facility and ranged from 70% to 74%, calculated with a six-month look-back period using the Rosendaal linear interpolation method. 41 …”
Section: Methodsmentioning
confidence: 99%
“…• С целью повышения эффективности лечения большинству пациентов с ФП рекомендуется пожизненное диспансерное наблюдение с периодичностью визитов к врачу как минимум 2 раза в год [509,510].…”
Section: профилактика и диспансерное наблюдение медицинские показания и противопоказания к применению методов профилактикиunclassified
“…• В рамках диспансерных осмотров пациентов с ФП рекомендуется регулярно оценивать наличие и динамику фоновых заболеваний и ФР с целью снижения риска осложнений [509,510].…”
Section: профилактика и диспансерное наблюдение медицинские показания и противопоказания к применению методов профилактикиunclassified